Theory of Multicomponent Separation Potential - Aleksandrov, Oleg Evgen’evich; Gadelshin, Vadim Maratovich (Current Chromatography, 2015)
A molecular-kinetic model of a multicomponent separation process has been suggested. The expression for multicomponent separation potential (the value function) has been obtained based on the “fundamental principles”. The feature of the separation process, which leads to an infinite value of the potential for pure components, has been discussed.
Keywords: separation potential